Galactomanana de Adenanthera pavonina Linn.: caracterização estrutural e atividade biológica na dislipidemia induzida por dieta hipercalórica em ratos - RODRIGUES, Daniele Gomes Cassias (2017)
The objective of the present study was to characterize the structural and functional properties of A. pavonina galactomannan seed and to evaluate its effect on hypercaloric diet induced dyslipidemia in rats. For this, the galactomannan was extracted from the seeds of A. pavonina, had its monosaccharide composition determined by Liquid Gas Chromatography, molecular weight and homogeneity determined by High Pressure Steric Exclusion Chromatography coupled to multidetectors, functional groups analyzed by FT-IR spectroscopy , rheological behavior analyzed in continuous shear, micromorphology analyzed by Scanning Electron Microscopy, and evaluation of the functional properties of water holding capacity (WHC) and oil (OHC). As regards the investigation of the effect of A. pavonina galatomannan on dyslipidemia, Wistar rats were randomly divided into four groups: GP (standard ration group) receiving Nuvilab®, GH (hypercaloric ration group), GHGA (group hypercaloric ration + galactomannan gel of A. pavonina) and GHGG (group hypercaloric ration + guar gum gel), which received a hypercaloric diet for 18 weeks to induce dyslipidemia. GHGA and GHGG were also simultaneously treated with 500 μL of gel at 5% of the respective galactomannan by gavage. After this period, the effects on weight gain, abdominal adiposity and serum and hepatic lipid profile were evaluated. Additionally, the effect of galactomannan on gastrointestinal motility was evaluated using models of gastric emptying and intestinal transit. In all experiments, guar gum, commercial galactomannan, was used as standard. The yield of the galactomannan extract was 19.62%, its mannose/ galactose ratio was 1.7: 1, presented a homogeneous elution profile in approximately 36 minutes, characteristic of polysaccharides, high molar mass (8.8 x 105 g molˉ¹), functional groups typical of galactomannans, non-Newtonian and pseudoplastic flow behavior, irregular, rough and porous micromorphological structure, and high rates of WHC (63.35 g H20/g sample) and OHC (3.04 g of oil/g of sample), comparable to those of the standard polymer. Regarding the effects on dyslipidemia, the GHGA group presented a lower percentage of weight gain in relation to GH (33.7 % vs 50.7 %), but did not avoid the accumulation of abdominal fat, similar to the GHGG group. The GHGA group also showed lower rates of serum triglycerides (52 mg/dL) and hepatic (32.5 mg/dL) and an increase in HDL-C (94.3 mg/dL) when compared to GH (96 mg/dL, 61.8 mg/dL, 52.4 mg/dL, respectively), while GHGG showed only effect on serum TG reduction. In addition, animals treated with A. pavonina galactomannan (57.7 %) and guar gum (62.5 %) showed a lower percentage of intestinal transit than those receiving only water (82.6 %), suggesting control satiety associated with reduced intestinal motility. The results indicate that A. pavonina galactomannan has a structure and functional properties similar to those of guar gum, and it is effective in the control of dyslipidemia, suggesting that A. pavonina galactomannan is an alternative source of soluble fiber with biotechnological potential similar to galactomannans traditionally used in the food, pharmaceutical industries and medical area.